Detection of Molds Which Present in Domestic's Refrigerators in Baghdad City - Ahmed Sahi Dwaish (Journal of Global Pharma Technology, 2017)
Twenty  species were isolated from 50 samples of domestic's refrigerators in Baghdad city , during September 2016 which were  Aspergillus niger, Aspergillus. flavus,  , Aspergillus. fumigatus, Aspergillus duricaulis , Aspergillus novofumigatus,  Aspergillus heteromorphus Aspergillus aculeatus , Aspergillus nidulans , Curvularia lunata ,Penicillium sp., Fusarium oxysporum,  , Alternaria alternate, Cladosporium sp.  Trichoderma sp., Mucor,  Rhizopus sp., Rhodotorula  mucilaginosa,  , Stachybotrys and yeast. Among the isolated species Aspergillus niger, was the most abundant (14.92%) followed by Aspergillus flavus (10.14%), while less abundant (0.95 & 0.63 %)  Cladosporium sp.  &., Mucor  respectively.